Identifying and Engineering Bottlenecks of Autotrophic Isobutanol Formation in Recombinant C. ljungdahlii by Systemic Analysis - Hermann, Maria; Teleki, Attila; Weitz, Sandra; Niess, Alexander; Freund, Andreas; Bengelsdorf, Frank Robert; Dürre, Peter; Takors, Ralf (Frontiers in Bioengineering and Biotechnology, 2021)
Clostridium ljungdahlii (C. ljungdahlii, CLJU) is natively endowed producing acetic acid, 2,3 butanediol, and ethanol consuming gas mixtures of CO2, CO, and H2 (syngas). Here, we present the syngas-based isobutanol formation using C. ljungdahlii harbouring the recombinant amplification of the ‘Ehrlich’ pathway that converts intracellular (KIV) to isobutanol. Autotrophic isobutanol production was studied analyzing two different strains in 3-L gassed and stirred bioreactors. Physiological characterization was thoroughly applied together with metabolic profiling and flux balance analysis. Thereof, KIV and pyruvate supply were identified as key ‘bottlenecking’ precursors limiting preliminary isobutanol formation in CLJU[KAIA] to 0.02 g L-1. Additional blocking of valine synthesis in CLJU[KAIA]::ilvE increased isobutanol production by factor 6.5 finally reaching 0.13 g L- 1. Future metabolic engineering should focus on debottlenecking NADPH availability, whereas NADH supply is already equilibrated in the current generation of strains.